Production technologies and formulation strategies in development of orodispersible tablets (ODTs) - Stevche Acevski; Angela Mircevska; Marija Glavas Dodov (Makedonsko Farmacevtski Bilten)
One of the new ways of drug delivery that is being developed more and more often recently is orodispersible tablets (ODTs), also known as orally disintegrating tablets, rapidly dissolving tablets and fast-dissolving tablets. The European Pharmacopoeia (Ph. Eur.) defines ODTs as uncoated tablets intended to be placed in the mouth where they disperse rapidly before swallowing, disintegrating within 3 minutes. ODTs come with many advantages such as: easy swallowability especially for paediatric, geriatric and bedridden patients, аs well as for people with lack of access to water; fast release of API and fast onset of action; and enhanced bioavailability. Мany of the novel drug delivery systems are difficult to scale-up and adapt to industrial production, and one of the many benefits of ODTs is that there are ways to manufacture them with conventional technology, which makes them cost-effective. All of these advantages lead to improved patient compliance. This review discusses the advantages and disadvantages of ODTs, the available production technologies including patented technologies, the main challenges in formulation of ODTs and different approaches for solving them, and where the research into ODTs as a novel drug delivery system is headed.